Utilization of amino acid for selective leaching of critical metals from spent hydrodesulfurization catalyst - Phann, Idol; Tanaka, Yu; Yamamoto, Sae; Okibe, Naoko (Frontiers in Chemistry, 2022)
While spent catalysts can cause serious environmental pollution, they can be considered an essential secondary metal source due to their high critical metal grades. The formation of the amino acid-metal complex is often seen in nature, and its potential application in hydrometallurgy can be foreseen. Alanine (Ala) was first screened as the most effective type of amino acid to be used for the selective leaching of spent hydrodesulfurization catalyst (consisting of MoS2 and Co3S4 supported on Al2O3, at 10% Mo and 2.4% Co grades). The sequential 3-step leaching (Step-1: Alkaline Ala leaching at 45°C, Step-2: Hot water leaching at 70°C, Step-3: Second alkaline Ala leaching at 45°C) was conducted where the role of Ala was found to be at least three-fold; 1) maintaining alkalinity by amino acid’s buffering capacity to assist Mo leaching, 2) selectively precipitating Co by forming Co-Ala complex with a distinctive pink color, which can readily re-dissolve in hot water to be separated from spent catalyst particles. 3) Effectively suppressing unwanted dissolution of Al throughout the reaction without needing pH control. Consequently, highly metal-selective, two separate Co-rich (<1% Mo and 79% Co dissolved, Al not detected) and Mo-rich (96% Mo, 19% Co, and 2.1% Al dissolved) leachates were obtained. This study highlighted the potential utility of amino acids as non-toxic, alternative metal lixiviant as well as a metal precipitant for selective leaching of critical metals from spent hydrodesulfurization catalyst.